2016
DOI: 10.1093/mnras/stw1881
|View full text |Cite
|
Sign up to set email alerts
|

Striations in molecular clouds: streamers or MHD waves?

Abstract: Dust continuum and molecular observations of the low column density parts of molecular clouds have revealed the presence of elongated structures which appear to be well aligned with the magnetic field. These so-called striations are usually assumed to be streams that flow towards or away from denser regions. We perform ideal magnetohydrodynamic (MHD) simulations adopting four models that could account for the formation of such structures. In the first two models striations are created by velocity gradients bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
5
35
1
Order By: Relevance
“…Striations, a network of faint and elongated density structures aligned along the magnetic field, are found in the low-column density (N H ≈ 1 − 2 × 10 21 cm −2 ) regions in MCs (Goldsmith et al 2008;Heyer et al 2016). The high velocity gradient transverse to the magnetic field compared to that along the field direction ) and the spatial power spectrum transverse to the magnetic field (Tritsis & Tassis 2016) provide strong observational evidence for anisotropic turbulent mixing as the mechanism of their formation.…”
Section: Examples For Low-density Parallel Filaments In the Ismmentioning
confidence: 97%
“…Striations, a network of faint and elongated density structures aligned along the magnetic field, are found in the low-column density (N H ≈ 1 − 2 × 10 21 cm −2 ) regions in MCs (Goldsmith et al 2008;Heyer et al 2016). The high velocity gradient transverse to the magnetic field compared to that along the field direction ) and the spatial power spectrum transverse to the magnetic field (Tritsis & Tassis 2016) provide strong observational evidence for anisotropic turbulent mixing as the mechanism of their formation.…”
Section: Examples For Low-density Parallel Filaments In the Ismmentioning
confidence: 97%
“…Heyer et al, 2016), where they appear as highly elongated along the magnetic field. Tritsis & Tassis (2016) have performed several numerical calculations to investigate their origin and concluded that they are most likely a consequence of non-linear MHD waves due to inhomogeneous density fields. Similar conclusion has been reached by Chen & Ostriker (2014) who presented a series of magnetized simulations and identified a network of small filaments aligned with the magnetic field in the simulations with the lowest β and estimate that this later must be < 0.2 to get prominent striations.…”
Section: Formation Of Filamentsmentioning
confidence: 99%
“…Magnetic fields also may play a role in feedback, for example, by driving protostellar jets that inject mass, momentum and energy into the medium, possibly stirring turbulent motions (Frank et al 2014;Gerrard et al 2019;Krumholz & Federrath 2019;. They also seem to play a role in the orientation of filamentary structures and striations in the MCs which may not directly influence the star-forming potential of the cloud, but certainly influences the global structure of the cloud through the density PDF (Planck Collaboration et al 2016a,b;Cox et al 2016;Malinen et al 2016;Soler et al 2017;Tritsis & Tassis 2016;Soler 2019). High-density filamentary structures house the local conditions necessary to overcome the turbulent motions, and observations find protostars located at junctions (or hubs) between intersecting filaments (André et al 2010;Men'shchikov et al 2010;Schneider et al 2013;Arzoumanian et al 2018;Tokuda et al 2018;Trevino-Morales et al 2019;Roy et al 2019;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%